KONSEP FITRAH MENURUT IBNU KHALDUN: ANALISIS KOMPARATIF DENGAN NATIVISME, EMPIRISME DAN KOVERGENSI - Muhammad Yani; Warul Walidin; Silahuddin (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2022)
This article discusses the concept of fitrah according to Ibn Khaldun and compares it with three theories of human development in educational psychology: Nativism, Empiricism, and Convergence. In Ibn Khaldun's view, humans are created with basic potentials that allow them to develop through education and social interaction. This potential, or fitrah, includes the ability to think, learn and build civilizations.Nativism emphasizes that human development is entirely determined by innate factors, while Empiricism holds the view that humans are born without any special potential and develop entirely from experience. Convergence combines both approaches.Through a qualitative approach and a literature study of Ibn Khaldun's Muqaddimah and educational psychology sources, this article shows that Ibn Khaldun's views are most in line with Convergence theory. He recognizes the existence of basic human potential (fitrah) as well as the importance of education and environment in actualizing this potential.With this analysis, this paper provides a cross-cultural understanding of human nature and opens a space for dialogue between classical Islamic thought and modern psychology